Analysis of Factors Affecting Purchase Intention and Price Premium for Purchasing Skincare Products in E-Commerce - Qadri, Rizni Aulia; Sutjiali, Florensia; Christiarini, Renny (Jurnal Ilmu Manajemen Advantage, 2025)
This study investigates the variables that affect price premium and buy intention in the beauty industry on Batam City's e-commerce platforms. In an era of increasing popularity of online shopping, understanding the key factors that influence consumer purchasing behavior in this channel is crucial. Data was collected by an online survey of users who have purchased Skincare products in E-commerce, and subsequently examined using PLS-SEM, or partial least squares structural equation modeling. The results of the analysis show that Trust has a significant influence on Purchase Intention and Premium Price, while Expertise, Brand Identity, and Brand Personality also have a significant influence on Trust. In the context of online shopping through e-commerce platforms, these findings offer crucial insights for marketers to create more successful marketing strategies by taking into account the attraction of expertise, brand identity, brand personality, and trust. It is anticipated that the findings of this research will offer meaningful insights and contribute significantly to the existing body of knowledge in the field to a more comprehensive understanding of consumer shopping behavior.